First-Line Molecular Genetic Evaluation of Autosomal Recessive Non-Syndromic Hearing Loss - Berk Özyılmaz; Gül Caner Mercan; Özgür Kırbıyık; Taha Reşid Özdemir; Samira Özkara; Özge Özer Kaya; Yaşar Bekir Kutbay; Kadri Murat Erdoğan; Merve Saka Güvenç; Altuğ Koç (Turkish Archives of Otorhinolaryngology, 2019)

(untitled)
Objective:The aim of this study is to investigate the efficiency of a first-line molecular genetic evaluation approach, in children with deafness.Methods:Patients who were found to have sensorineural hearing loss by age-appropriate audiological tests were selected for the molecular genetic evaluation. The molecular genetic evaluation was carried out with GJB2 gene sequence analysis and mtDNA m.1555A>G mutation Restriction Fragment Length Polymorphism (RFLP) analysis. Additionally, in a small group of patients, hearing loss Multiplex Ligation-dependent Probe Amplification (MLPA) analysis was done out to identify the possible role of copy number changes.Results:In this Turkish cohort, which included 104 index patients and 78 relatives, 33 (31.7%) had Pathogenic/Likely Pathogenic variants. One or more GJB2 sequence variants were identified in 46 (44.1%) of the 104 index patients. The homozygous c.35delG mutation by itself explained the etiology in 24% of our ARSNHL group. In one (5%) of the 20 patients of MLPA group, a hemizygous deletion in POU3F4 gene was detected.Conclusion:In our Turkish cohort, we applied a first-line molecular genetic evaluation approach using GJB2 gene sequence analysis and mtDNA m.1555A>G RFLP analysis. This approach revealed the genetic etiology of 44.1% of our index patients. Additionaly, the results of hearing loss MLPA analysis revealed the limited role of copy number changes in this patient group. Furthermore, with a detailed genotype-phenotype association workup, 2 rare cases of Deafness with Palmoplantar Hyperkeratosis and Keratitis-Ichthyosis-Deafness syndrome were reported.